Manganese import protects Salmonella enterica serovar Typhimurium against nitrosative stress. Issue 11 (20th October 2020) - Yousuf, Shehla; Karlinsey, Joyce E.; Neville, Stephanie L.; McDevitt, Christopher A.; Libby, Stephen J.; Fang, Ferric C.; Frawley, Elaine R.
Abstract : In response to nitric oxide, Salmonella typhimurium acquires manganese and exports zinc, magnesium and iron. Uptake is driven by expression of transporters MntH and SitABCD as well as by ZupT. Abstract : Nitric oxide (NO˙) is a radical molecule produced by mammalian phagocytic cells as part of the innate immune response to bacterial pathogens. It exerts its antimicrobial activity in part by impairing the function of metalloproteins, particularly those containing iron and zinc cofactors. The pathogenic Gram-negative bacterium Salmonella enterica serovar typhimurium undergoes dynamic changes in its cellular content of the four most common metal cofactors following exposure to NO˙ stress. Zinc, iron and magnesium all decrease in response to NO˙ while cellular manganese increases significantly. Manganese acquisition is driven primarily by increased expression of the mntH and sitABCD transporters following derepression of MntR and Fur. ZupT also contributes to manganese acquisition in response to nitrosative stress. S. Typhimurium mutants lacking manganese importers are more sensitive to NO˙, indicating that manganese is important for resistance to nitrosative stress.